Kem Anak Hebat and Fun Islami (KAHFI): Program Pelatihan Kreatifitas dan Pembinaan Agama Anak-Anak Indonesia di Kuala Lumpur - Cut Muftia Keumala; Neny Triana; Maisyuri Maisyuri; Subhan Ramadhan; Agam Wildan; Rina Ridara (Sekolah Tinggi Ilmu Administrasi Nasional, 2023)
The Creative Training and Religious Guidance Program for Indonesian Muslim Children in Kuala Lumpur is important because access to Islamic religious education and Quranic studies in Kuala Lumpur is considered expensive and inaccessible to lower-income Indonesian children. This program aims to provide equal opportunities for children from lower-income backgrounds to obtain quality religious education and develop creative skills. In a diverse environment like Kuala Lumpur, it is important for Indonesian Muslim children to strengthen their religious understanding to maintain their religious identity and practice Islamic values in their daily lives. However, the high costs associated with religious education and Quranic studies can be a barrier for children from families with limited incomes. The Creative Training and Religious Guidance Program for Indonesian Muslim Children in Kuala Lumpur is designed to address this constraint. By collaborating with educational institutions and religious organizations like Fatayat Nahdatul Ulama (NU), the program offers training in creative skills, such as arts and music, while providing religious guidance to the children. This provides an opportunity for children from lower-income backgrounds to access affordable Islamic education and Quranic studies. The program has dual benefits. First, children can access Islamic religious knowledge and learn to recite the Quran without a heavy financial burden, thereby reducing the disparity in access to religious education. Second, by aligning activities with the spirit of Ramadan, the program creates an environment that ignites the enthusiasm of children to participate and enhances their love for Islam. This program offers a new hope for children from lower-middle-class backgrounds in Indonesia to develop a solid understanding of their religion and strengthen their Muslim identity.